Measuring environmental performance of turkic republics with multicriteria decision making methods - Karahan, Mehmet; Yildirim, Turgay; Yildirim, Zafer (Gazi Univ, 2025)
This study reassesses the environmental performance of the Turkic Republics using the 2024 Environmental Performance Index (EPI) data with Multi-Criteria Decision Making (MCDM) methods. CRITIC, Standard Deviation and MEREC methods are used to determine the criteria weights, followed by TOPSIS, ARAS and CRADIS methods to rank the countries. The results reveal certain deviations from the traditional EPI ranking, indicating that T & uuml;rkiye performed better under the multi-criteria decisionmaking (MCDM) methods. While Kazakhstan and Uzbekistan generally exhibited the strongest overall performance, Azerbaijan and Kyrgyzstan ranked lower. Despite having the lowest performance in the EPI ranking, T & uuml;rkiye secured the top position under the TOPSIS method. The study underscores the necessity for more comprehensive analyses to support countries in enhancing their environmental sustainability policies and highlights the potential significance of regional cooperation. Notably, water resources emerged as one of the most critical determinants of environmental performance. The findings suggest that traditional rankings may have certain limitations, whereas MCDM methods provide a more balanced and holistic framework for decision-making. In this context, it is recommended that regional structures such as the Organization of Turkic States enhance environmental cooperation to make sustainability policies more effective.
Keywords: Environment; Environmental Performance; EPI; MCDM